EU Plans for a CO2 Border Adjustment - Fritz Söllner (Wirtschaftsdienst)
Abstract The Carbon Border Adjustment Mechanism proposed by the European Commission will only be able to prevent part of carbon leakage. It will cause high costs and fail to create incentives for non-EU countries to lower their carbon emissions. The mechanism is not compatible with WTO principles and will cause trade conflicts from which Germany, due to its high export surpluses, will suffer most. Therefore, the proposal of the Commission should not be realised. Instead, to compensate for the competitive disadvantages of EU industry, the tried and proven system of allocating free ETS certificates should be continued.